Analisis strategi manajemen dalam program perlindungan kesehatan universal di thailand - Rizka Husnia Kanti (Publisia: Jurnal Ilmu Administrasi Publik, 2020)
This study discusses about the analysis of management strategies in the universal health coverage program in Thailand. Universal health coverage is a health facility program in Thailand that addresses all communities without determining their socioeconomic status. This program was launched since 2001. This has led the Thai government to make a big breakthrough by launching a universal health coverage program. This research is a qualitative research using secondary data sources and data collection methods using literature study methods. Data processing is done by selecting journals through various sources until selected into five journals. The analysis used in this study is the theory of strategy management according to Bozeman and Straussmen by measuring three indicators of goals and objectives, developing an action plan that can mediate between the organization and the environment, and using effective implementation methods.DOI: 10.26905/pjiap.v5i1.3868